2021
DOI: 10.1051/0004-6361/202039648
|View full text |Cite
|
Sign up to set email alerts
|

The role of stochastic and smooth processes in regulating galaxy quenching

Abstract: Context. Galaxies can be classified as passive ellipticals or star-forming discs. Ellipticals dominate at the high end of the mass range, and therefore there must be a mechanism responsible for the quenching of star-forming galaxies. This could either be due to the secular processes linked to the mass and star formation of galaxies or to external processes linked to the surrounding environment. However, the contribution from these smooth and stochastic processes to galaxy quenching has yet to be quantified. Ai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…These authors showed that the dominant mechanism is inside-out quenching where quenching first takes place in the central region and then proceeds outwards. This effect is dominant for central galaxies and highmass satellites, but is weaker for low-mass satellites with stellar masses logM * < 10.5 (see also Kipper et al 2021). This agrees well with our results, which showed that the percentage of galaxies with log M * < 10.5 is lower than 20 % among satellite galaxies with D n (4000) > 1.75, and there are almost no BGGs with such low stellar mass.…”
Section: Does Global Density Matter?supporting
confidence: 92%
See 1 more Smart Citation
“…These authors showed that the dominant mechanism is inside-out quenching where quenching first takes place in the central region and then proceeds outwards. This effect is dominant for central galaxies and highmass satellites, but is weaker for low-mass satellites with stellar masses logM * < 10.5 (see also Kipper et al 2021). This agrees well with our results, which showed that the percentage of galaxies with log M * < 10.5 is lower than 20 % among satellite galaxies with D n (4000) > 1.75, and there are almost no BGGs with such low stellar mass.…”
Section: Does Global Density Matter?supporting
confidence: 92%
“…Typically, it takes more than one peripassage to quench a satellite galaxy. The star formation in galaxies deceases under environmental processes described as slow-then-rapid quenching with characteristic timescales of 4 − 5 Gyr (Muzzin et al 2014;McGee et al 2014;Maier et al 2019;Kipper et al 2021;Kuschel et al 2022). Slow quenching by strangulation and overconsumption starts when a galaxy enters a group and gas inflow stops.…”
Section: Coevolution Of Galaxies and Groups In The Cosmic Webmentioning
confidence: 99%
“…Another scenario is the 'slow-then-rapid' quenching (see e.g. Maier et al 2019;Roberts et al 2019;Kipper et al 2021), whereby galaxies undergo slow quenching processes and, once they enter a dense environment, start a faster quenching phase. Results from Pallero et al (2022), using the C-EAGLE simulation support this scenario.…”
Section: On the Pre-processing Scenariomentioning
confidence: 99%
“…( 10) but implemented with different grids in kernel K. The g indexes the likelihoods, and G is the number of grids averaged per likelihood evaluation. A more thorough description is provided in Kipper et al (2021) in the context of modelling galaxy evolution.…”
Section: Improving Statistical Descriptionmentioning
confidence: 99%